2018
DOI: 10.1016/j.jvs.2017.08.081
|View full text |Cite
|
Sign up to set email alerts
|

Superior mesenteric artery calcification is associated with cardiovascular risk factors, systemic calcified atherosclerosis, and increased mortality

Abstract: SMAC is associated with specific CVD risk factors as well as with calcification in all other arterial beds. SMAC extent was significantly associated with incident cardiovascular mortality, whereas both SMAC presence and extent were significantly associated with all-cause mortality, even after adjustment for risk factors and calcification in other arterial beds. Further studies are needed to determine whether SMAC is simply a marker for advanced and systemic disease or whether it confers increased mortality ris… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 9 publications
1
17
0
Order By: Relevance
“…However, different studies show that the presence of calcifications in the celiac trunk or in the superior mesenteric artery correlates with systemic calcified atherosclerosis, cardiovascular risk factors, all-cause mortality, and fatty liver. This could be in favor of an atherosclerotic process in these arteries [14,31,32].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, different studies show that the presence of calcifications in the celiac trunk or in the superior mesenteric artery correlates with systemic calcified atherosclerosis, cardiovascular risk factors, all-cause mortality, and fatty liver. This could be in favor of an atherosclerotic process in these arteries [14,31,32].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, it has been known for more than a century that atherosclerosis and other vascular anomalies are more often seen in the intrapancreatic vessels of patients with diabetes than in control subjects [12,13]. A recent study showed that the extent of calcifications in the superior mesenteric artery associates with the presence of diabetes [14]. In a postmortem angiography study, it was shown that vascular anomalies are more often seen in patients with type 2 diabetes than in control subjects, independently from the duration of diabetes [15].…”
Section: Introductionmentioning
confidence: 99%
“…Among our study participants, coronary calcification co-occurred with atherosclerotic plaques in the carotid and/or femoral arteries in 87.8% in close agreement with the previous result. About more generalized arterial calcification one study found that calcification of the superior mesenteric artery was significantly associated with the calcification of five other arterial territories (celiac trunk, coronaries, thoracic aorta, abdominal aorta, and iliac arteries) on CT [ 35 ]. Another study found that more than two-thirds of patients over 70 years old showed generalized arterial calcification in all investigated arteries (carotid, coronary, aorta, iliac arteries) and calcified atherosclerotic plaques significantly correlated in different vascular beds [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…Lin et al had previously reported that the SMA calcification has a strong association with major cardiovascular risk factors, cardiovascular mortality, and all-cause mortality. 17 Renal artery calcification had also been shown to have strong association with all-cause mortality in healthy individuals, independent of traditional cardiac risk factors. 18 Both studies were performed on a healthy population with no known cardiovascular disease.…”
Section: Discussionmentioning
confidence: 99%